Bank Owners or Bank Managers: Who is Keen on Risk? Evidence from the Financial Crisis - Reint E. Gropp; Matthias Köhler (Verein für Socialpolitik, 2010)
In this paper, we analyse whether bank owners or bank managers were the driving force behind the risks incurred in the wake of the financial crisis of 2007/2008. We show that owner controlled banks had higher profits in the years before the crisis, and incurred larger losses and were more likely to require government assistance during the crisis compared to manager-controlled banks. The results are robust to controlling for a wide variety of bank specific, country specific, regulatory and legal variables. Regulation does not seem to mitigate risk taking by bank owners. We find no evidence that profit smoothing drives our findings. The results suggest that privately optimal contracts aligning the incentives of management and shareholders may not be socially optimal in banks.
Keywords: G21; G30; G34; 330; Banks; risk taking; corporate governance; ownership structure; financial crisis